Moral Position In Legal Science: An Analysis of The Dynamics of Legal Science Development - Heru Siswanto (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
The emphasis of moral principle lies in the beneficial purpose of law subjected to lengthy problems regarding the placement. Different analyses have been carried out relating to the effects of natural law and positivism in legal science. Therefore, this study aims to achieve an understanding of the position of moral principle in legal science in the dynamics of legal development. The results show that moral principle assumes a significant role in legal science in the context of natural law theory. Conversely, positivism suggests the purification of legal constructs from moral components, emphasizing the need to remain detached from moral principles.